2018
DOI: 10.3389/fvets.2018.00253
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing of Mycobacterium bovis Isolated From Livestock in the United States, 1989–2018

Abstract: The United States official bovine tuberculosis (bTB) eradication program has utilized genotyping for Mycobacterium bovis isolates since 2000 and whole genome sequencing was implemented in 2013. The program has been highly successful, yet as bTB prevalence has reached historic lows, a small number of new bTB-affected cattle herds occur annually. Therefore, understanding the epidemiology of bTB transmission is critically important, in order to target limited resources for surveillance and achieve eradication. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 29 publications
1
75
0
4
Order By: Relevance
“…S1). Three of the strains were isolated in 2009 from primates that were placed in quarantine upon entering the United States (23,24). Their genomes grouped together with the M. caprae genomes on the phylogeny and shared the lepA V424V marker for this species (25).…”
mentioning
confidence: 99%
“…S1). Three of the strains were isolated in 2009 from primates that were placed in quarantine upon entering the United States (23,24). Their genomes grouped together with the M. caprae genomes on the phylogeny and shared the lepA V424V marker for this species (25).…”
mentioning
confidence: 99%
“…Nevertheless, attained results suggest that M. bovis strains are likely to cluster based on geographical location (Dippenaar et al, 2017; Kraemer Zimpel et al, 2017; Lasserre et al, 2018). In our previous study, we have also shown that few M. bovis genomes do not carry any CC genetic marker (Zimpel et al, 2017a), a phenomenon that was recently observed in M. bovis isolates from one cattle herd in the USA and from slaughterhouse cattle in Eritrea (Ghebremariam et al, 2018; Orloski et al, 2018b). These findings suggest that CCs are unlikely to represent the whole diversity of M. bovis strains, warranting further evaluation of M. bovis molecular lineages (Zimpel et al, 2017a; Lasserre et al, 2018).…”
Section: Introductionmentioning
confidence: 71%
“…Since the whole-genome sequence of the first M. bovis strain became available in 2003 (Garnier et al, 2003), increasing efforts have been made to sequence additional strains and use whole-genome information to tackle bovine and/or wildlife TB transmission within specific outbreaks or countries (Bruning-Fann et al, 2017; Sandoval-Azuara et al, 2017; Ghebremariam et al, 2018; Kohl et al, 2018; Lasserre et al, 2018; Orloski et al, 2018a; Price-Carter et al, 2018; Razo et al, 2018). However, no studies to date have comprehensively analyzed M. bovis genomes at a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, pode contribuir nas abordagens epidemiológicas moleculares como parte integrante do rastreamento e da disseminação da bTB. A fonte de infecção é desconhecida para aproximadamente metade dos rebanhos afetados pela bTB, e os resultados da WGS neste estudo podem sugerir várias fontes possíveis, incluindo movimentação de bovinos não documentado, animal importado e utilização de produtos não pasteurizados como o colostro infectado por M. bovis fornecido coletivamente aos bezerros de um mesmo rebanho (PALMER et al, 2013;ORLOSKI et al, 2018).…”
Section: Bibliotecas Genômicas E Sequenciamentounclassified
“…A possibilidade de monitorar mutações no genoma bacteriano permite rastrear o espalhamento da doença entre animais e propriedades e estruturar modelos de redes de contatos entre as populações. A combinação de conhecimentos epidemiológicos com os dados do WGS tem sido estratégica para as investigações sobre a dinâmica da tuberculose bovina, destacando aspectos importantes e ainda não quantificados, como a extensão da transmissão entre as espécies e a taxa de substituição (ORLOSKI et al, 2018;PRICE-CARTER et al, 2018;SALVADOR et al, 2019a). A técnica de WGS tem sido utilizada como estratégia de vigilância para a erradicação, visando o rastreamento de focos e estudos epidemiológicos no Reino Unido (BIEK et al, 2012;TREWBY et al, 2016), Estados Unidos (BRUNING-FANN et al, 2017;ORLOSKI et al, 2018;SALVADOR et al, 2019b), Nova Zelândia (CRISPELL et al, 2017;PRICE-CARTER et al, 2018) e Alemanha (KOHL et al, 2018c).…”
Section: Introductionunclassified